PERMINTAAN ENERGI LISTRIK DI JAWA TENGAH - Mudakir, Bagio (Universitas Muhammdaiyah Surakarta, 2007)
This study is intended to determine factors influencing the demand of electricity energy in Central Java. The increasing demand of energy might create a shortage or crisis due to a relatively constant of energy supply. It is because a very high costs for constructing energy power plants. The increasing energy demand over economic growth might create a question, what is the influence of economic activities toward the demand of electricity energy. It is also a problem whether energy demand utilizedas production factor in the economy or consumed as final goods.